Impedance-based microfluidic cytometry for label-free monitoring and on-demand microcarrier sorting - Gong, Lingyan (Nanyang Technological University, 2024)
In cell-based manufacturing, three-dimensional (3D) cell cultures, including spheroids (cellular aggregates), microcarriers and hydrogel microparticles (~100-300 µm) are widely used for scaled-up cell expansion and cell processing in tissue engineering, cell therapies, etc. Conventional bioprocess sensors measure culture medium bulk properties (e.g. gases, pH, temperature, metabolites) to monitor biomass indirectly which provide limited information on cell heterogeneity and product quality. This advocates an unmet need to develop novel in-line monitoring methodologies to enable accurate monitoring of cell growth and cell quality (size, viability etc.) in continuous bioprocesses. In this PhD thesis, we first developed a novel multi-frequency microfluidic impedance cytometry device for label-free monitoring of cellular properties of single spheroids, Cytodex microcarriers and cell-encapsulated hydrogel microparticles. Two impedance signatures namely 1) low-frequency impedance (|ZLF|) and 2) opacity defined as the ratio of high-frequency impedance to low-frequency impedance (|ZHF|/|ZLF|), were defined to assess biomass and cell viability at single particle resolution. Using breast cancer (MCF-7) spheroids and HaCaT cell-encapsulated hydrogel particles, we demonstrated that |ZLF| increased with biomass, while higher opacity indicated cell death due to compromised cell membrane. Anti-cancer drug (Paclitaxel)-treated spheroids exhibited lower |ZLF| with increased cell dissociation. Interestingly, adipose-derived mesenchymal stem cell (ADSC) differentiation on Cytodex-3 microcarriers exhibited higher impedance magnitude when differentiating into adipocytes due to intracellular lipid content, and higher opacity when differentiating into osteoblasts due to calcium deposition and changes in membrane components. To achieve continuous harvesting of cellular products, the device is integrated with a real-time piezo-actuated particle sorter based on user-defined multi-frequency impedance signatures. We first performed biomass profiling of Cytodex-3 microcarriers seeded with adipose-derived mesenchymal stem cells (ADSCs) to sort well-seeded or confluent microcarriers for downstream culture or harvesting, respectively. Next, we demonstrated impedance-based isolation of microcarriers with osteogenic differentiated ADSCs which was validated with a two-fold increase of calcium content in sorted ADSCs. Impedance profiling of heterogenous ADSCs-encapsulated hydrogel (alginate) microparticles and 3D ADSC aggregate mixtures was also performed to sort particles with high biomass and cell viability to improve cell quality. Overall, the scalable microfluidic platform technology enables in-line sample processing from bioreactors directly and automated analysis (up to 200 particles/sec) of cell quality attributes and on-demand sorting (up to 10 particles/sec) to maximize cell yield and improve the control of cell quality in continuous cell-based manufacturing.